ORIGIN AND FUNCTION OF THE GURU - Leidecker, Kurt F (Journal of Dharma, 1986)
The concept of guru as spiritual friend and guide with all its melioristic and pejorative aspects has, since its inception, undergone many changes, conditioned largely by circumstances social, economic and cultural. In examining the earliest and pre-Buddhistic literature of India it will appear that highly personal concepts had also cosmic overtones which then were lost in later periods. To get at the root of the concept under discussion it is necessary to layaway some of the traditional well-worn ideas in comparative religion text books about various forms of theism and priestcraft and, if possible, practice a little empathy with man of the Vedic period.